Impact of trade liberalization and fluctuations of commodity prices on government finances : the case of Saint Lucia (ECLAC Port of SpainTT, 1999)
Provides an assessment of the effects of trade liberalization and fluctuations in banana prices on government finances in Saint Lucia. Highlights the importance of banana exports to the economy.
Keywords: TRADE LIBERALIZATION